IMPLEMENTASI STANDAR AKUNTANSI PEMERINTAH TERHADAP LAPORAN KEUANGAN DAERAH DINAS PEKERJAAN UMUM BINA MARGA PROVINSI JAWA TIMUR - Anggara, Uga Bayu; Jannah, Binti Shofiatul (Cahaya Ilmu Bangsa, 2024)
This research aims to obtain an overview of the application of Government Accounting Standards (SAP) to financial reports in accordance with Government Regulation Number 71 of 2010 in the East Java Province Public Works Department of Highways. Using qualitative descriptive methods, data was collected through field studies with observations and interviews. The research results show that the East Java Province Public Works Department of Highways has carried out financial reporting well. This can be seen from the fact that before submitting a transfer request, the employee who is responsible for the financial report has planned what needs need to be purchased within Panjar, and has followed the procedures and provisions in preparing the financial report to be sent.